Multi‐Responsive Bottlebrush‐Like Unimolecules Self‐Assembled Nano‐Riceball for Synergistic Sono‐Chemotherapy. Issue 3 (2nd September 2020) - Shi, Xiaoxiao; Zhang, Yang; Tian, Ye; Xu, Shuyu; Ren, En; Bai, Shuang; Chen, Xiaoyuan; Chu, Chengchao; Xu, Zhigang; Liu, Gang
Abstract: Improved drug loading content, bioavailability, and controlled release in targeted tissue have been major bottlenecks in the design of precision nanomedicine. Herein, a tumor‐specific and multiple‐stimuli responsive nano‐riceball is proposed and validated for enhanced sono‐chemotherapy. The nano‐riceball (NGR@DDP) possesses a well‐designed core‐shell structure, formed by an inner core assembly that contains ultrasound/H2 O2 responsive bottlebrush‐like unimolecular dextran‐POEGMA9 ‐ b ‐PMTEMA22 (DOS) with co‐loaded doxorubicin and Purpurin 18. This inner core of NGR@DDP is further buried by a "striffen" of NGR (Asn‐Gly‐Arg)‐modified RBC‐membrane derived from CRISPR‐engineered mice. As a result, nano‐riceball NGR@DDP is featured with high drug stuffing content (30.3 wt%), low critical micelle concentration (5.93 µg mL −1 ), and intelligent exogenous ultrasound/endogenous H2 O2 stimuli‐triggered precise drug release at tumor site. Under fluorescence/photoacoustic imaging guidance, combined sonodynamic therapy and chemotherapy exhibit excellent synergistic effect, and dramatically inhibit the growth of orthotopic HepG2 hepatocellular carcinoma with negligible side effects. This nano‐riceball strategy provides a facile way to achieve function hybridization for personalized nanomedicine. Abstract : Tumor tissue‐specific and multiple‐stimuli responsive nano‐riceball NGR@DDP are prepared with improved drug bioavailability, controlled release, and enhanced synergistic sono‐chemotherapy. This nanotheranostic strategy provides a facile way to achieve function hybridization for personalized nanomedicine.